2019
DOI: 10.1002/chem.201805032
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing RbPbBr3 Perovskite Nanocrystals through Cs+ Substitution

Abstract: ABX3‐type halide perovskite nanocrystals (NCs) have been a hot topic recently due to their fascinating optoelectronic properties. It has been demonstrated that A‐site ions have an impact on their photophysical and chemical properties, such as the optical band gap and chemical stability. The pursuit of halide perovskite materials with diverse A‐site species would deepen the understanding of the structure–property relationship of the perovskite family. In this work we have attempted to synthesize rubidium‐based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The X‐ray diffraction patterns of RbPbBr 3 in Figure c confirm the phase transition from non‐perovskite to perovskite at 290 °C, which agrees well with theoretical simulations. According to the XRD results in Figures c, Figures c and d, the non‐perovskite phase dominates in the directly obtained samples; the main phase of the annealed samples was transformed to a perovskite structure . Figure d depicts the PL and absorption spectra of perovskite‐phase RbPbBr 3 .…”
Section: Figurementioning
confidence: 94%
See 3 more Smart Citations
“…The X‐ray diffraction patterns of RbPbBr 3 in Figure c confirm the phase transition from non‐perovskite to perovskite at 290 °C, which agrees well with theoretical simulations. According to the XRD results in Figures c, Figures c and d, the non‐perovskite phase dominates in the directly obtained samples; the main phase of the annealed samples was transformed to a perovskite structure . Figure d depicts the PL and absorption spectra of perovskite‐phase RbPbBr 3 .…”
Section: Figurementioning
confidence: 94%
“…The tolerance factor of RbPbBr 3 is about 0.78 (the effective ionic radii of Rb + , Pb 2+ , and Br − are 1.61, 1.19, and 1.96 Å, respectively). This indicates that RbPbBr 3 perovskite structures are hard to realize and have poor stability . The incorporation of Cs + into RbPbBr 3 will lead to a larger tolerance factor and stabilize the perovskite phase.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Finite Rb + incorporation results in further tilting of the PbX 6 octahedra, reducing the overall orbital overlap and hence opening up the bandgap of CsPbBr 3 while simultaneously reducing the tolerance factor . However, it has been reported that an upper bound of 70% Rb + exists in a mixed cation perovskite QD, as pure RbPbBr 3 does not exist under ambient conditions …”
Section: Peled Electroluminescence Performance Metricsmentioning
confidence: 99%